Investigating the Effects of Second Language Background, Proficiency, and Usage on Episodic Memory in Middle-Aged and Older Adults. - Fares, Bassam Jeryous; Taler, Vanessa (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2026)
As the aging population grows, it is important to investigate factors that protect against cognitive decline. Bilingualism is hypothesized to contribute to cognitive reserve. However, the research on the influence of bilingualism and related variables (e.g., age of second language [L2] acquisition and language usage) on episodic memory remains sparse. We investigate the role of L2 age of acquisition, proficiency, and usage on verbal and nonverbal episodic memory in middle-aged and older adult bilingual speakers of English and French. Accuracy on a verbal memory task was negatively associated with L2 usage at work. People with lower L2 proficiency and usage at home performed better on a nonverbal memory task in terms of accuracy and reaction time, respectively. Earlier L2 acquisition was associated with higher accuracy on the nonverbal memory task. We hypothesize that greater L2 engagement leads to increased effort to inhibit nonrelevant stimuli, impeding episodic memory retrieval, and the effort required is lower with earlier L2 acquisition.